5-aminosalicylic acid dependency in Crohn's disease: a Danish Crohn Colitis Database study - Duricova, Dana; Pedersen, Natalia; Elkjaer, Margarita; Jensen, Jens K Slott; Munkholm, Pia (Journal of Crohn's & colitis, 2010)
BACKGROUND AND AIMS: The role of 5-aminosalicylic acid (5-ASA) in Crohn's disease is unclear. The outcome of the first course of 5-ASA monotherapy with emphasis on 5-ASA dependency was retrospectively assessed in consecutive cohort of 537 Crohn's disease patients diagnosed 1953-2007. METHODS: Following outcome definitions were used: Immediate outcome (30 days after 5-ASA start) defined as complete/partial response (total regression/improvement of symptoms) and no response (no regression of symptoms with a need of corticosteroids, immunomodulator or surgery). Long-term outcome defined as prolonged response (still in complete/partial response 1 year after induction of response); 5-ASA dependency (relapse on stable/reduced dose of 5-ASA requiring dose escalation to regain response or relapse ≤1 year after 5-ASA cessation regaining response after 5-ASA re-introduction). RESULTS: One hundred sixty-five (31%) patients had monotherapy with 5-ASA. In 50% 5-ASA monotherapy was initiated ≤1 year after diagnosis (range 0-49 years). Complete/partial response was obtained in 75% and no response in 25% of patients. Thirty-six percent had prolonged response, 23% developed 5-ASA dependency and 38% were non-responders in long-term outcome. Female gender had higher probability to develop prolonged response or 5-ASA dependency (OR 2.89, 95%CI: 1.08-7.75, p=0.04). The median duration (range) of 5-ASA monotherapy was 34 months (1-304) in prolonged responders, 63 (6-336) in 5-ASA dependent and 2 (0-10) in non-responders. CONCLUSIONS: A selected phenotype of Crohn's disease patients may profit from 5-ASA. Fifty-nine percent of patients obtained long-term benefit with 23% becoming 5-ASA dependent. Prospective studies are warranted to assess the role of 5-ASA in Crohn's disease.
Keywords: antiflogistika nesteroidní; Male; spotřeba léčiv; Treatment Outcome; Time Factors; lidé středního věku; retrospektivní studie; senioři nad 80 let; Aged, 80 and over; Crohnova nemoc; Sex Factors; časové faktory; Phenotype; Humans; Middle Aged; senioři; mužské pohlaví; Female; nemocnice univerzitní; mladiství; Aged; Hospitals, University; Anti-Inflammatory Agents, Non-Steroidal; ženské pohlaví; Retrospective Studies; Denmark; mladý dospělý; Adult; Young Adult; mesalamin; sexuální faktory; Drug Utilization; Mesalamine; Adolescent; dospělí; Dánsko; lidé; fenotyp; Crohn Disease; výsledek terapie